Involvement of GABAergic and Adrenergic Neurotransmissions on Paraventricular Nucleus of Hypothalamus in the Control of Cardiac Function - Mendonça, Michelle M.; Santana, Joice S.; da Cruz, Kellen R.; Ianzer, Danielle; Ghedini, Paulo C.; Nalivaiko, Eugene; Fontes, Marco A. P.; Ferreira, Reginaldo N.; Pedrino, Gustavo R.; Colugnati, Diego B.; Xavier, Carlos H. (Frontiers in Physiology, 2018)
Sympathetic premotor neurons of the paraventricular hypothalamus (PVN) play a role in hemodynamics adjustments during changes in body fluid homeostasis. However, PVN contribution to the tonic control of cardiac function remains to be systematically studied. In this study, we assessed whether gabaergic and adrenergic synapses, known for being active in the PVN, are involved in the control of cardiac function. Adult male Wistar rats (250-350 g; n=27) were anesthetized with urethane (1.2-1.4 g/kg i.p.) and underwent catheterization of femoral artery to record blood pressure and heart rate. The femoral vein was used to inject the vasoactive agents phenylephrine (10 µg/kg) and sodium nitroprusside (10 µg/kg) and to supplement anesthesia. The cardiac left ventricle was catheterized to record left ventricular pressure and its derivative. Craniotomy allowed for injections (100 nL) into the PVN of: muscimol (20 mM), bicuculline methiodide (0.4 mM), propranolol (10 mM), isoproterenol (100 µM), phentolamine (13 mM), phenylephrine (30 nM). We found that: i) inhibition of PVN by muscimol, reduced arterial pressure, cardiac chronotropy and inotropy; ii) disinhibition of PVN neurons by bicuculline evoked positive chronotropy and inotropy, and increase blood pressure; iii) PVN alpha adrenergic receptors control cardiac chronotropy and inotropy; iv) beta adrenergic receptors of the PVN do not influence cardiac function; v) afterload does not contribute to the PVN-evoked inotropy. Our results indicate that the modulation of the activity of PVN neurons exerted by gabaergic and adrenergic mechanisms contribute to the control of cardiac function.